Lumbar tactile acuity is near identical between sides in healthy pain-free participants - Wand, B.M.; Catley, M.J.; Luomajoki, H.A.; O'Sullivan, K.J.; Harrington, Flavia; O'Connell, N.E.; Moseley, G.L. (CHURCHILL LIVINGSTONE, 2014)
A growing body of literature suggests that alterations in brain structure and function are a feature of chronic back pain. Tactile acuity is considered a clinical signature of primary somatosensory representation and offers a simple measure of cortical reorganisation. Clinical interpretation of test scores from an individual patient is hampered by variance in published normative values and less than ideal inter-rater reliability. These problems might be mitigated in people with unilateral back pain by using the patient as their own control and comparing tactile acuity at the painful site to performance at the corresponding position on the non-painful side. The first step in exploring this approach is to quantify the normal side-to-side difference in healthy populations. We pooled data from three previous studies that measured lumbar tactile acuity bilaterally in healthy controls using similar protocols. We calculated the mean and variance of the absolute error between sides, the standard error of measurement and the reliable change index (RCI). The mean difference between sides was 3.2mm (±5.2) when assessed vertically and 1.9mm (±3.2) when assessed horizontally. The standard error of measurement was 4.2mm when assessed vertically and 2.7mm when assessed horizontally. The RCI suggests that differences of greater than 13mm when assessed horizontally and 17mm when assessed vertically equate to 95% confidence that a difference truly exists. Several assumptions related to the application of this approach need to be investigated further.